2007
DOI: 10.1016/j.trstmh.2007.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic renal failure in North Central Province of Sri Lanka: an environmentally induced disease

Abstract: This study was conducted to determine the aetiology of chronic renal failure (CRF) in the North Central Province of Sri Lanka. Patients (n=183) with CRF of unknown aetiology were compared with controls (n=200) who had no evidence of chronic renal dysfunction. Exposure to possible risk factors were determined by an interviewer-administered questionnaire. Being a farmer (P<0.001), using pesticides (P<0.001), drinking well water (P<0.001), a family history of renal dysfunction (P=0.001), use of ayurvedic treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
108
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 6 publications
4
108
1
6
Order By: Relevance
“…Irrespective of the causative factor(s) of CKD-mfo, the renal tubular damage occurs in patients at an early stage of the disease [17]; with time; it causes irreversible renal fibrosis leading to renal failure and premature death [6,17,24]. Once kidneys are fibrosed, the damage is irreversible, so prevention is the only way forward.…”
Section: Postulated Causes For Ckd-mfomentioning
confidence: 99%
“…Irrespective of the causative factor(s) of CKD-mfo, the renal tubular damage occurs in patients at an early stage of the disease [17]; with time; it causes irreversible renal fibrosis leading to renal failure and premature death [6,17,24]. Once kidneys are fibrosed, the damage is irreversible, so prevention is the only way forward.…”
Section: Postulated Causes For Ckd-mfomentioning
confidence: 99%
“…Based on CKDu's clinical profile and risk factors, it was postulated that environmental toxins which affect vulnerable groups in a specific geographical area contribute to the onset and progression of the disease [7]. Several investigators have explored the aetiological contribution of exposure to various environmental toxins such as pesticides, microbial toxins and heavy metals [6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…CKDu mainly affects farming communities with poor socioeconomic background [5]. The estimated prevalence of CKDu in a community based study was reported as 16.9% in women and 12.9% in men, but the severe stages were seen more frequently in men, leading to a higher mortality and morbidity in men [5,6].Based on CKDu's clinical profile and risk factors, it was postulated that environmental toxins which affect vulnerable groups in a specific geographical area contribute to the onset and progression of the disease [7]. Several investigators have explored the aetiological contribution of exposure to various environmental toxins such as pesticides, microbial toxins and heavy metals [6,[8][9][10].…”
mentioning
confidence: 99%
“…Thus, it has been named CKD of uncertain etiology (CKDu). The majority of CKDu patients in the NCP are from the low socioeconomic farming community [8]. As a result of the insidious onset and progression of the disease, these patients present in the late stages, which requires renal replacement therapy such as dialysis and transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…In this CKDu endemic region, an epidemiological survey to evaluate the possible risk factors has revealed that a family history of CKDu, taking ayurvedic treatment, and a history of snake bite are significant predictors for CKDu occurrence [8]. As a result of the clinically observed heterogeneity in disease progression, we hypothesized that the rate of disease progression and death could be modified by different demographic, clinical, and lifestyle-related factors.…”
Section: Introductionmentioning
confidence: 99%